Review artikel: Pemanfaatan jaminan kesehatan ibu dan anak dalam pelayanan persalinan di puskesmas kabupaten atau kota di Indonesia - Salman, Salman; Hilmi, Indah Laily; Oktavianti, Alfina; Salsabila, Isyana; Lestari, Sepiyani Ayu; Putria, Devy Kasih; Windari, Welly (Journal of Pharmaceutical and Sciences, 2024)
Universal Health Coverage (UHC) is one of the government's targets in public health services to the Sustainable Development Goals (SDGs). The UHC is a crucial and urgent resolution for all nations to expand health systems with equal access and affordable costs. The program is one of the efforts to lower the maternal and infant mortality rate. As a healthcare provider, public health centers must ensure optimal care and services. Public health centers realize that providing health care refers to the core health efforts program. This research aims to analyze maternal and child health insurance use in maternity services in Public health centers. The analysis uses the study methodology of the literature review library with search engines used in literature searches such as Google Scholar and PubMed with the keywords Birth Assurance, Public Health Centers, Sustainable Development Goals, and Universal Health Coverage. The survey results show that the use of maternity guarantees for the population in Public health centers in terms of efficiency, effectiveness, responsiveness, uniformity, and accuracy still needs to be better achieved. The research identifies differences between people's expectations of quality of health care and the realities experienced, focusing on the various dimensions that make up quality of service. These dimensions include reliability, responsiveness, assurance, empathy, and tangible. The conclusion of this study suggests that services in Public health centers should be continuously improved through capacity improvements, improvements or renovations of infrastructure and systems, as well as some programs with preventive, promotional, and empowerment of the public to UHC.